IMPLEMENTASI SISTEM INFORMASI DATA PEMILIH DALAM PENETAPAN DATA AKURAT OLEH KOMISI PEMILIHAN UMUM PADA PEMILIHAN WALI KOTA BITUNG TAHUN 2024 - Vionia Charlize Monica Pangkerego; Johny Peter Lengkong; Johnly Roycke Pangemanan; Jusuf Johanes Wowor; Yurnie Sendow (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The study aims to analyze the implementation of the Voter Data Information System (SIDALIH) in establishing accurate voter data in the 2024 Bitung Mayor Election. This investigation utilizes a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation. Informants include election commissioners, SIDALIH operator, sub district election committees, and registered voters. The analytical framework uses George C. Edwards III’s policy implementation theory focusing on communication, resources, disposition, and bureaucratic structure. The outcomes reveal that SIDALIH contributes significantly to improving voter data accuracy through duplicate detection, updating voter elements, and synchronization with the civil registry database. However, challenges remain, including internet connectivity limitations, varying of population administration data. A case involving a foreign citizen included in the voter list highlights weaknesses in substantive citizenship verification. Overall, SIDALIH implementation in Bitung is relatively effective but requires stronger institutional coordination, improved system integration, and continuous human resource development to enhance the integrity of voter data in future elections.